A Multi-Criteria Analysis of University Housing Options using Weighted Sum Model - Muhammad Ade Kurnia Harahap; Ira Modifa Tarigan; Kraugusteeliana Kraugusteeliana; Sanco Simanullang; Ernie C. Avila; Robbi Rahim (JINAV: Journal of Information and Visualization, 2023)
This study presents a novel application of the Multi-Criteria Decision-Making (MCDM) Weighted Sum Model (WSM) technique to assist students in selecting suitable university housing options. We identified five key criteria—location, affordability, amenities, room type, and social environment—based on a survey of prospective students' preferences. Using the Analytic Hierarchy Process (AHP), we calculated the weights for each criterion, reflecting the priorities of the surveyed students. We then applied the MCDM-WSM methodology to rank the housing options by calculating the weighted scores for each criterion. Our findings reveal a ranked list of university housing options that can guide students in making well-informed decisions based on their needs and preferences. The study demonstrates the significance of using advanced decision-making techniques in transforming complex decision-making processes into more structured, transparent, and reliable approaches. Furthermore, it highlights potential research gaps and future research directions to enhance the quality of choices and cater to the diverse needs of students in selecting university housing.